Response of Silybum marianum plant to irrigation intervals combined with fertilization - SABER F. HENDAWY; MOHAMED S. HUSSEIN; ABD-ELGHANI A. YOUSSEF; REYAD A. EL-MERGAWI (Nusantara Bioscience, 2013)
Abstract. Hendawy SF, Hussein MS, Youssef AA, El-Mergawi RA. 2013. Response of Silybum marianum plant to irrigation intervals combined with fertilization. Nusantara Bioscience 5: 22-29. This study was investigated to evaluate the influence of different kinds of organic and bio fertilization under different irrigation intervals on the growth, production and chemical constituents of Silybum marianum plant. Data indicated that all studied growth and yield characters were significantly affected by the duration of irrigation intervals. Fertilizer treatments had a primitive effect on growth and yield characters. The interaction between irrigation intervals and fertilizer treatments has a clear considerable effect on growth and yield characters. The obtained results indicated the favorable effect of organic and bio fertilizers which reduce the harmful effect of water stress. Different treatments had a pronounced effect on silymarin content.